Operational risk modelling and management - Franzetti, Claudio (Boca Raton : CRC Press, 2011)
"In banking regulation, tools are needed to quantify risk and calcul ate the amount of capital reserve required to mitigate such risk. This book offers a complete model for the quantification of so-called operat ional risks. It offers a detailed discussion on the link between modeli ng approaches and management, which has been neglected in the literatur e, as well as the mathematical modeling of the loss distribution approa ch. With an emphasis on risk management and management fundamentals, th e text presents a complete simulation model along with tested examples that can be replicated using R software. The author provides a broad vi ew on managing risk using this mathematical model"--
"A Chapman & Hall book."
Includes bibliographical references (p. 361-380) and index.
Keywords: Risk management; Risk management -- Mathematical models